THE EFFECT OF CONTENT MARKETING ON CUSTOMER ENGAGEMENT WITH VIRAL MARKETING AS INTERVENING VARIABLES (Study on Shopee Users in Bandar Lampung City) - Ridho, Pandu Muhammad; hartono, Hartono; Aprilia, Hani Damayanti (Jurnal Kompetitif Bisnis, 2022)
This study aims to determine the effect of content marketing on customer engagement of shopee users in the city of Bandar Lampung with viral marketing as an intervening variable. The type of research is explanatory research with a quantitative approach. The population of this study is shopee users in the city of Bandar Lampung. The data was obtained from questionnaires filled out online. The sampling technique used purposive sampling with a total sample of 100 respondents. Data analysis in this study used path analysis and Sobel test using SPSS 25. Based on the results of research and analysis showed that content marketing has a positive and significant effect on viral marketing, viral marketing has a positive and significant impact on customer engagement, content marketing has a positive and significant effect on viral marketing. significant positive effect on customer engagement and content marketing but not significant on customer engagement through viral marketing (Partial Mediation).